Self-efficacy as a moderator of the effect of techno-pedagogical competence on economics teachers' readiness - Oroh, Silvana Shirly Alice; Arsana, I Kadek Satria; Dolonseda, Herman Philips (Indonesian Journal of Educational Development (IJED), 2025)
Teachers' readiness to teach in the digital era presents a strategic challenge for 21st-century education. This study examines the effect of TPC on economics teachers' TR, with SE as a moderating variable. Using a quantitative explanatory design, data were collected via questionnaires from 204 senior and vocational high school economics teachers in Minahasa Regency, who were purposively selected. The data were analyzed with SEM-PLS. The results confirm that TPC significantly influences both SE and TR. SE also has a significant positive effect on TR and demonstrates a moderating role, strengthening the relationship between TPC and TR. The model shows moderate to substantial predictive power, with R² values of 0.468 for SE and 0.597 for TR. These findings highlight that teacher development programs should not only prioritize technical competence but also foster self-efficacy as a psychological resource for effective digital teaching readiness. The study is limited by its focus on one region and subject area, as well as its reliance on self-reported quantitative data. Future research should adopt a longitudinal approach and expand to other contexts to better capture the complexity of teachers’ readiness in the digital era.